Conformational Properties and Orientational Order of a de Vries Liquid Crystal Investigated through NMR Spectroscopy. Issue 7 (31st January 2014) - Domenici, Valentina; Lelli, Moreno; Cifelli, Mario; Hamplova, Vera; Marchetti, Alessandro; Veracini, Carlo Alberto
Abstract Solid‐state and liquid‐state NMR spectroscopic techniques are used to describe at molecular level the behaviour of a de Vries liquid crystal (namely the mesogen 9HL) at the SmA–SmC* transition, which is characterized by the absence of the layer shrinkage, typical of non‐de Vries smectogens. Previous 2H NMR studies on the same smectogen, performed at a different magnetic field (from 4.70 to 18.80 T), provided evidence of the occurrence of a tilt of one of the three phenyl rings, constituting the aromatic core of 9HL, at the SmA–SmC* phase transition. In this work, the study is extended to the whole rigid aromatic core of the 9HL. In particular, the variable temperature behavior of the mesogen studied by 1D 13C NMR cross‐polarization (CP) and 2D 1H–13C PDLF (proton‐encoded 13C‐detected, local field) NMR experiments made possible the characterization of the conformational and orientational properties in the two smectic phases. These results are compared with various proposed models invoked to describe the SmA–SmC* transition in de Vries smectogens at a molecular level.